Estudio molecular de las poblaciones de un lodo anaerobio en condiciones desnitrificantes y metanogénicas - Martínez Gutiérrez, Emir (Universidad Autónoma Metropolitana, 2004)
In nature the microbial populations form communities or consortia, which interact among them. Each population is related with the others and contribute to the survival of the whole populations. However, up to now it is not well understood which are the kind of mechanisms involved in the maintenance of viability of the consortia. It is also though that when the environmental conditions change, the microbial population also change by means of a succession of different microorganisms or microbial populations. It is also said that when the environmental conditions are modified, rather than the microbial change, a metabolic change or genetic exchanges are seen among the microbial population. In the present work it was operated a reactor with a denitrifying sludge during 229 days. The carbon nitrogen ratio (C/N) was of 1.4. The N2 production rate was of 455±43 mg/ Ld. As the respiratory rate had a low variation the denitrification was under steady state. At these conditions the nitrate consumption efficiency was of 99.86% and the molecular nitrogen yield close to 1. In this all period of time a samples were taken to carried out the quantification of microorganisms using the more probable number (MPN) technique and later molecular analysis. A this same sludge was evaluated under methanogenic conditions, but the nutritional and the C/N ratio was fitted from 1.4 to 30. Under these new conditions the steady state was reached as the methane production rate was 283±21.8 mg C-CH4 /L d. The effectiveness of the system was similar to that found in the denitrifying sludge. The MPN for determining the denitrifying and methanogenic populations showed that the former was bigger than the latter in two order of magnitude (6.9 X 1010, 8.4 X 108 bacteria / gVSS, respectively) throughout the denitrifying process. During the methanogenic process the methanogenic population was four order of magnitude higher than the denitrifying one. These results suggest that the change of the environmental conditions from denitrification to methanogenic, the denitrifying population decrease one order of magnitude, while the methanogenic population increased five orders of magnitude The microbial analysis using the RAPD technique showed that the pattern bands changed, indicating that the kind of microorganisms also changed. The band patterns indicated that denitrifying populations decreased and increased the methanogenic population when the environmental changed from denitrifying to methanogenic process. The hybridizing analysis using the nirS prove showed a similar results. Namely, during the methanogenic process the denitrifying population decreased because the prove did not detect the corresponding gene.; En la naturaleza, las poblaciones microbianas que conforman una comunidad, o consorcios, interactúan entre sí, y cada población contribuye al mantenimiento de la misma, pero todavía hay muchas interrogantes acerca de los mecanismos involucrados que permiten la viabilidad del consorcio. También se piensa que cuando hay un cambio de condiciones ambientales hay cambios en la población a través de una sucesión de microorganismos distintos o de poblaciones microbianas. Hay también evidencias que señalan que, más que cambio en la población, puede haber un cambio metabólico de la población según las condiciones ambientales; o bien llevarse a cabo intercambios genéticos entre las poblaciones del consorcio. En el presente trabajo, se operó un reactor con lodo desnitrificante, bajo condiciones desnitrificantes durante 220 días. La relación carbono nitrógeno (C/N) fue de1.4. La velocidad de producción de N2 fue de 455±43 mg/ Ld, por lo que la velocidad respiratoria estuvo en estado estacionario. En estas condiciones las eficiencia de consumo de nitrato fue de 99.86% y el rendimiento de nitrógeno molecular fue cercano a 1. Se tomaron muestras del lodo durante todo ese periodo, para cuantificar la población por medio del número mas probable (NMP) y su análisis molecular posterior. Al mismo lodo se le cambiaron las condiciones de cultivo a metanogénicas, mediante el ajuste nutricional y el cambio de la C/N de 1.4 a 30. Se alcanzó el estado estacionario con una velocidad de producción de metano de 283±21.8 mg C-CH4 /L d. La efectividad del sistema fue similar a la del lodo desnitrificante. Se tomaron muestras del lodo para analizarlas molecularmente más tarde. El NMP, para cuantificar la población desnitrificante y metanogénica, mostró que la población desnitrificante fue superior en dos ordenes de magnitud, respecto a la metanogénica, (6.9 X 1010, 8.4 X 108 bacterias / gSSV, respectivamente) en el proceso desnitrificante. En el proceso metanogénico la población metanogénica fue superior en cuatro ordenes de magnitud con respecto a la desnitrificante. Estos resultados mostraron, que al cambiar las condiciones del reactor de desnitrificante a metanogénico, la población desnitrificante disminuye un orden de magnitud. Mientras que la población metanogénica, tuvo un cambio más grande, al aumentar cinco ordenes de magnitud su número. De acuerdo al análisis por RAPD mostró que en el patrón de las bandas hubo un cambio en el número de microorganismos, ya que hubo una disminución de la población desnitrificante y un aumento de la metanogénica, cuando se cambió de proceso desnitrificante a metanogénico. El análisis de hibridación con la sonda correspondiente al gen nirS indicó resultados similares. La población desnitrificante disminuye durante la metanogénesis, ya que no es detectada con la sonda.